Trends in the EU bioeconomy 2023 - Mubareka, Sarah B.,Giuntoli, J.,Sánchez López, J.,Lasarte-López, J.,M'barek, Robert,Ronzon, T.,Renner, A.,Avraamides, M. (Publications Office of the European Union, 2023)
Policy monitoring frameworks allow decision makers to assess the performance and progress towards specific strategic objectives that reflect an overall vision. The bioeconomy consists of complex social, economic, and environmental systems. The EU Bioeconomy Monitoring System was developed by the JRC to fulfil the need for a holistic policy monitoring framework and track economic, environmental and social progress towards a sustainable bioeconomy through relevant indicators. Here we present the first assessment based on the EU Bioeconomy Monitoring System.
10.2760/835046
Keywords: Graue Literatur; Amtliche Publikation; Bioökonomik; EU-Staaten; sustainable development; economic indicator; environmental indicator; social indicator; decision-making; EU regional policy; EU policy; EU programme; macroeconomics; food security; natural resources; energy efficiency; renewable energy; adaptation to climate change; competitiveness; job creation; EU study report